Type-1 angiotensin receptor signaling in central nervous system myeloid cells is pathogenic during fatal alphavirus encephalitis in mice. Issue 1 (December 2016) - Blakely, Pennelope; Huber, Amanda; Irani, David
Abstract Background Alphaviruses can cause fatal encephalitis in humans. Natural infections occur via the bite of infected mosquitos, but aerosol transmissibility makes some of these viruses potential bioterrorism agents. Central nervous system (CNS) host responses contribute to alphavirus pathogenesis in experimental models and are logical therapeutic targets. We investigated whether reactive oxygen species (ROS) generated by nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (Nox) activity within the CNS contributes to fatal alphavirus encephalitis in mice. Methods Infected animals were treated systemically with the angiotensin receptor-blocking drug, telmisartan, given its ability to cross the blood-brain barrier, selectively block type-1 angiotensin receptors (AT1R), and inhibit Nox-derived ROS production in vascular smooth muscle and other extraneural tissues. Clinical, virological, biochemical, and histopathological outcomes were followed over time. Results The importance of the angiotensin II (Ang II)/AT1R axis in disease pathogenesis was confirmed by demonstrating increased Ang II levels in the CNS following infection, enhanced disease survival when CNS Ang II production was suppressed, increased AT1R expression on microglia and tissue-infiltrating myeloid cells, and enhanced disease survival in AT1R-deficient mice compared to wild-type (WT) controls. Systemic administration of telmisartan protected WT mice from lethal encephalitis caused by two different alphaviruses in a dose-dependent manner without altering virus replication or exerting any anti-inflammatory effects in the CNS. Infection triggered up-regulation of multiple Nox subunits in the CNS, while drug treatment inhibited local Nox activity, ROS production, and oxidative neuronal damage. Telmisartan proved ineffective in Nox-deficient mice, demonstrating that this enzyme is its main target in this experimental setting. Conclusions Nox-derived ROS, likely arising from CNS myeloid cells triggered by AT1R signaling, are pathogenic during fatal alphavirus encephalitis in mice. Systemically administered telmisartan at non-hypotensive doses targets Nox activity in the CNS to exert a neuroprotective effect. Disruption of this pathway may have broader implications for the treatment of related infections as well as for other CNS diseases driven by oxidative injury.